Circadian Rhythm Disorders and Melatonin Production in 127 Blind Women with and without Light Perception. (June 2014) - Flynn-Evans, Erin E.; Tabandeh, Homayoun; Skene, Debra J.; Lockley, Steven W.
Light is the major environmental time cue that synchronizes the endogenous central circadian pacemaker, located in the suprachiasmatic nuclei of the hypothalamus, and is detected exclusively by the eyes primarily via specialized non-rod, non-cone ganglion cell photoreceptors. Consequently, most blind people with no perception of light (NPL) have either nonentrained or abnormally phased circadian rhythms due to this inability to detect light. Conversely, most visually impaired participants with some degree of light perception (LP) exhibit normal entrainment, emphasizing the functional separation of visual and "nonvisual" photoreception. The aims of the study were to identify the prevalence of circadian disorders in blind women, with the further aim of examining how eye disease may relate to the type of circadian disorder. Participants ( n = 127, age 50.8 ± 13.4 years) completed an 8-week field study including daily sleep diaries and sequential 4 to 8 hourly urine collections over 48 h on 2 to 3 occasions separated by at least 2 weeks. Circadian type was determined from the timing and time course of the melatonin rhythm measured by cosinor-derived urinary 6-sulfatoxymelatonin rhythm peak. Of the participants with NPL ( n = 41), the majority were abnormally phased (24%) or nonentrained (39%), with 37% classified as normally entrained. Of the participants with LP ( n = 86), the majority were normally entrained (69%). Eighteen LP participants (21%) were abnormally phased (8 advanced, 10 delayed). Nine LP participants (10%) were nonentrained. The eye conditions most associated with abnormal phase and/or nonentrained circadian rhythms were bilateral enucleation (67%) and retinopathy of prematurity (57%). By contrast, 84% of participants with retinitis pigmentosa and 83% of those with age-related macular degeneration were normally entrained. These findings suggest that the etiology of blindness in addition to LP status is related to an individual's ability to process the circadian light signal.